Effect of treat-to-target strategies on maternal and neonatal outcomes of rheumatoid arthritis: a multicentre real-world ANSWER cohort study - Hiramatsu, Yuri; Kotani, Takuya; Nakamura, Eri; Yoshikawa, Ayaka; Hashimoto, Motomu; Onishi, Akira; Murata, Kouichi; Yamamoto, Natsuki; Murakami, Kosaku; Hirano, Toru; Maeda, Yuichi; Ebina, Kosuke; et al. (Rheumatology, 2026)
Objectives We evaluated real-world disease activity, treatment patterns and pregnancy outcomes in women with rheumatoid arthritis (RA) utilizing a multicentre Japanese cohort. Feasibility and impact of a treat-to-target (T2T) approach during pregnancy were also examined. Methods A retrospective observational study analysed 118 pregnancies in patients with RA from the multicentre ANSWER cohort (2013–2023) across eight Japanese academic institutions. Clinical characteristics, treatment regimens and RA Disease Activity Scores of 28 joints based on C-reactive protein (DAS28-CRP) were assessed at preconception, during each trimester and postpartum. Pregnancy and neonatal outcomes were analysed. Results Of 118 pregnancies, 92.8% achieved full-term deliveries (median birthweight: 2949g). Remission or low disease activity was maintained in ∼85% of patients throughout pregnancy, with increased postpartum disease activity. Patients who continued biologic diseasemodifying antirheumatic drugs (bDMARDs) during pregnancy (n=35) exhibited significantly lower DAS28-CRP scores during the second and third trimesters compared with those who discontinued (n=24) (P =0.007 and P =0.0002, respectively). Etanercept or certolizumab pegol use was associated with favourable disease control. Tocilizumab (n=6) or abatacept (n=2) was not associated with adverse maternal or neonatal outcomes. Glucocorticoid use was associated with increased disease activity. Salazosulfapyridine use correlated with increased birth weight (P =0.003) and gestational age (P =0.051). Conclusion T2T management, including selective continuation of bDMARDs, was associated with favourable maternal disease control and reassuring pregnancy outcomes. Although the absence of long-term follow-up is a limitation, these findings provide real-world evidence supporting this approach. Larger prospective studies are required to confirm maternal and neonatal safety beyond the early postpartum.
CRIS-Team Scopus Importer:2026-02-13
Keywords: biologic DMARDs; neonatal outcomes; pregnancy; rheumatoid arthritis; treat-to-target